PEMBUATAN MINYAK KELAPA DARI SANTAN DENGAN CARA ELEKTROKIMIA - Titik Mahargiani; I Ketut Subawa (Eksergi, 2010)
Coconut palm is a very usefitl plant. Almost every parts of the tree can be used by people. The most important part is its fruit. From coconut fruit we can get its oil as oil-water emulsion with protein emulsion fier. Coconut oil is the most value part of coconút fruit. Oil content of coconut fruit is 34,7 %. In order to extract its oil front the fruit, we can use electrochemical way. First the fruit make into coconut milk and then coconut milkput inlo electrochemical tool. Electrochemical is a process in which colloid particles are moved under influence of electric current, When a pair of electrodes are given electric current, the protein which has function as a emulsifìer will be destroyed and it causes the separaction oil from wøter. Good relativity condition is reached in : electrochemical time 60 minules, electric current 4 ampere, cathode width 40 cm2 and the coconut oil result is 38.5 ml, the presentage oil result I I % equivalent to 0,01103 mgrek / granr oil free futty acid oil